SYNTHESIS AND CHARACTERIZATION OF AMINE(CHLOR0)COBALOXIME DERIVATIVES. APPROXIMATE VALUES OF THE ANGULAROVERLAP PARAMETER, ?, FOR THE COORDINATED AMINES (Journal of Sciences, Islamic Republic of Iran)
Four new complexes of the type [LCo ((DO)(DOH) pn) Cl] PF , where (DO) (DOH) pn = N , N '- propanediylbis (2, 3-butanedione2-imine3-oxirne)a nd L =morpholine (mrpln) (I), benzylamine (bzlan) (II), piperidine (pprdn)(III) and pyrrolidine (prldn) (IV) have been synthesized and characterized by elemental analyses and spectroscopic methods. Approximate values of the angular-overlap parameter, ?, for the coordinated amines are estimated to be: 6395,6627,6797, and 7076 cm for mrpln, bzlan, pprdn, and prldn, respectively